2018
DOI: 10.1111/gwat.12643
|View full text |Cite
|
Sign up to set email alerts
|

How or When Samples Are Collected Affects Measured Arsenic Concentration in New Drinking Water Wells

Abstract: Naturally occurring arsenic can adversely affect water quality in geologically diverse aquifers throughout the world. Chronic exposure to arsenic via drinking water is a human health concern due to risks for certain cancers, skin abnormalities, peripheral neuropathy, and other negative health effects. Statewide in Minnesota, USA, 11% of samples from new drinking water wells have arsenic concentrations exceeding 10 μg/L; in certain counties more than 35% of tested samples exceed 10 μg/L arsenic. Since 2008, Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The total modeled area is about 50,000 km 2 . The two study regions each have complex glacial geology overlying bedrock (Figure and previously described in Erickson et al, ). The unconsolidated sediments in the regions are composed of deposits from multiple glacial advances and retreats, the last occurring during the late Pleistocene period, 16,000–12,000 years ago (Lusardi, ).…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
“…The total modeled area is about 50,000 km 2 . The two study regions each have complex glacial geology overlying bedrock (Figure and previously described in Erickson et al, ). The unconsolidated sediments in the regions are composed of deposits from multiple glacial advances and retreats, the last occurring during the late Pleistocene period, 16,000–12,000 years ago (Lusardi, ).…”
Section: Hydrogeologic Settingmentioning
confidence: 99%
“…The concentration of SO 4 2− in groundwater was considered less prone to sorption, precipitation and geochemical reduction (Kim et al, 2017). Erickson et al (2018) observed that the concentration of As in groundwater from new wells was highly variable relative to that found when sampled months later. Although the concentrations of PTEs were lower than the drinking water quality guidelines (WHO, 2017), some (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, field filtration of samples was reported to influence the measured concentration of several trace elements in water [75]. Filtered samples generally cause less variability of groundwater As concentration in a well compared to unfiltered samples [76].…”
Section: Data Quality Assessment and Preparation Of The Working Datasetmentioning
confidence: 99%